Analisis Penerapan Model Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kritis pada Pembelajaran IPA di SDN 10 Limboto - Siti Nur Jannah Bakri; Yulanti S. Mooduto; Andi Nur Syarif Hidayatullah (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the implementation of the discovery learning model in improving students’ critical thinking skills in science learning at SDN 10 Limboto. This study employed a qualitative descriptive approach. The research subjects consisted of the principal, teachers, and students of grades IV, V, and VI. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that the implementation of the discovery learning model was carried out through the stages of stimulation, problem statement, data collection, data processing, verification, and generalization. This model encouraged active student engagement and contributed to the development of critical thinking skills, including the ability to provide explanations, formulate strategies, conduct observations, process information, and draw conclusions. The development of critical thinking skills was found to progress across grade levels. However, the implementation has not been fully optimal due to several challenges, such as differences in student abilities, uneven participation, and limitations in processing and communicating information. Therefore, the discovery learning model has the potential to improve students’ critical thinking skills, although its implementation requires further optimization to achieve more effective outcomes.